Ancient ocean crossings : reconsidering the case for contacts with the pre-Columbian Americas - Jett, Stephen C., 1938- (The University of Alabama Press, 2017)
In Ancient Ocean Crossings: Reconsidering the Case for Contacts with the Pre-Columbian Americas, Stephen Jett encourages readers to reevaluate the common belief that there was no significant interchange between the chiefdoms and civilizations of Eurasia and Africa and peoples who occupied the alleged terra incognita beyond the great oceans. More than a hundred centuries separate the time that Ice Age hunters are conventionally thought to have crossed a land bridge from Asia into North America and the arrival of Columbus in the Bahamas in 1492. Traditional belief has long held that earth's two hemispheres were essentially cut off from one another as a result of the post-Pleistocene meltwater-fed rising oceans that covered that bridge. The oceans, along with arctic climates and daunting terrestrial distances, formed impermeable barriers to interhemispheric communication. This viewpoint implies that the cultures of the Old World and those of the Americas developed independently. Drawing on abundant and concrete evidence to support his theory for significant pre-Columbian contacts, Jett suggests that many ancient peoples had both the seafaring capabilities and the motives to cross the oceans and, in fact, did so repeatedly and with great impact. His deep and broad work synthesizes information and ideas from archaeology, geography, linguistics, climatology, oceanography, ethnobotany, genetics, medicine, and the history of navigation and seafaring, making an innovative and persuasive multidisciplinary case for a new understanding of human societies and their diffuse but interconnected development.